Lycopodina hystrix Ekins & Erpenbeck & Goudie & Hooper 2020, sp. nov. - Ekins, Merrick; Erpenbeck, Dirk; Goudie, Lisa; Hooper, John N. A. (Zenodo, 2020)
Lycopodina hystrix sp. nov. urn:lsid:zoobank.org:act: 0D895565-2580-4D22-9916-22BA8FD4BECE Lycopodina sp. 1, Ekins, Erpenbeck & Hooper, 2020: Table 14. Material Examined: Holotype: SAMA S2599, Yatala Canyon, Commonwealth Marine Reserve, Great Australian Bight, South Australia, VSM 02, 34 o 47’ 57” S 131 o 45’ 20” E, 1393 m, Remotely Operated Vehicle (ROV), Coll. CSIRO on RV Rem Etive, Cruise RE2017 _ CO1, Sample VSM02 _014_105, 17 March 2017. Paratype: SAMA S2600 same collection data as SAMA S2599, Sample VSM02 _014_106, 17 March 2017. Paratype: SAMA S3559 same collection data as SAMA S2599, Sample VSM02 _014_105.1, 17 March 2017. Distribution : Endemic to the Great Australian Bight, South Australia, bathyal depth. Etymology : L. hystrix, porcupine, named for its spiky appearance. Description. Growth form : Erect, clavate-shaped body, with a very hispid array of filaments arising at all angles from the body, supported by a short stem and disc-shaped basal attachment (Fig. 7 A). The holotype, SAMA S2599, measures 18 mm in total length, with the sponge body 6 mm diameter, 9 mm long, and 3.4 mm in depth. The filaments extend for at least 4.5 mm from the body. Paratype SAMA S3559 is attached to a piece of Madrepora oculata Linnaeus, 1758, and has a total length of 7 mm, with the remains of the body only 2 mm in length, and the filaments extend 2 mm away from the body. Paratype SAMA S2600 has a total length of 10 mm, body 2 mm wide, 6 mm long and external filaments of almost 3 mm. Colour : On-deck the body, stem, basal disc and base of the filaments were white, with the tips of the filaments appearing to have red and orange colouring, mostly due to detritus. After preservation in ethanol the sponges were cream in colour. Ectosomal skeleton : A thin membranous ectosome covers all of the sponge, with anisochelae found only in the ectosome of the main body. Endosomal skeleton : The skeleton consists of several bundles of longitudinal styles forming the central axis. These extend from the base of the stem to the top of the sponge body (Fig. 7 N–O). At right angles to the core bundles are very long filaments several times longer than the width of the body. These consist of styles not only at right angles to the body but also buttressed by styles at an acute angle to the filaments (Fig. 7 O). The basal attachment has echinating styles extending through the ectosome (Figure 7 P). Megascleres: Megascleres consist of five categories of styles-tylostyles. Mycalostyles 1 of the body, filaments and stem have long tapering points and gradually tapering bases, with the thickest part of the spicule approximately one third towards the basal end. Oxeote styles 2 are nearly anisoxeote, with the basal end rapidly tapering to nearly a point. Styles echinating the base of the stem and basal disc range from small tylostyles 3, small styles 4, large, thin styles 5, and in one specimen only strongyles (see Table 3). Microscleres : The microscleres consist of a single size class of palmate anisochelae and forceps. The anisochelae has a single upper large frontal alae nearly completely detached from the two lateral alae which are completely fused to the shaft, and two smaller lower alae nearly completely fused. The lower alae also has three blunt teeth with a central dominant tooth, and the other small alae directly behind it has four blunt teeth, arranged in pairs of unequal sizes. Chelae are 10.5–16 µm long. Forceps ribbon-shaped with tight central curvature expanding out to wider curvature approximately one third along the basal end, dimensions 30–51 x 3–11 µm (see Table 3). Rare sigmancistras 9–13 x 0.1–1.3 µm (see Table 3). Molecular data: We were unable to obtain sufficient material for DNA analysis. Remarks : Amongst the fifteen current species of Lycopodina that have forceps (see Ekins, Erpenbeck & Hoop- er 2020), this new species is closest to L. occidentalis (Lambe, 1893) from the Pacific coast of Canada in skeletal structure with multiple axial bundles, having different morphologies of styles localised to different regions of the sponge, and the size of anisochelae and forceps. However, L. hystrix sp. nov. has a very different clavate morphology than the stipitate L. occidentalis , and different megasclere geometries. With the exclusion of the forceps this species otherwise resembles the descriptions of L. callithrix (Hentschel, 1914) from Antarctica as redescribed by Goodwin et al . (2017), although this new species has a distinct ectosomal skeleton, differentiated spicule localisation, and lacks the very long 2–4 mm styles/subtylostyles that characterise L. callithrix. The new species also differs from L. helios Ekins, Erpenbeck & Hooper, 2020 by possession of forceps, being at least twice its size, having an elongated shaped body, and most obviously by the concentrated radial spikes, which in L. hystrix sp. nov. are easily the size of the body, whilst those of L. helios , only just emerge slightly from the ectosome of the body. : Published as part of Ekins, Merrick, Erpenbeck, Dirk, Goudie, Lisa & Hooper, John N. A., 2020, New carnivorous sponges and allied species from the Great Australian Bight, pp. 240-266 in Zootaxa 4878 (2) on page 252, DOI: 10.11646/zootaxa.4878.2.2, http://zenodo.org/record/4424977 : {"references": ["Ekins, M., Erpenbeck, D. & Hooper, J. N. A. (2020) Carnivorous sponges from the Australian Bathyal and Abyssal zones collected during the RV Investigator 2017 Expedition. Zootaxa, 4774 (1), 1 - 159. https: // doi. org / 10.11646 / zootaxa. 4774.1.1", "Lambe, L. M. (1893 [1894]) Sponges from the Pacific coast of Canada. Proceedings and Transactions of the Royal Society of Canada, 11 (4), 25 - 43, pls. II-IV.", "Hentschel, E. (1914) Monaxone Kieselschwamme und Hornschwamme der Deutschen Sudpolar-Expedition 1901 - 1903. Deutsche Sudpolar-Expedition, 15 (1), 35 - 141, pls. IV-VIII.", "Goodwin, C. E., Berman, J., Downey, R. V. & Hendry, K. R. (2017) Carnivorous sponges (Porifera: Demospongiae: Poecilosclerida: Cladorhizidae) from the Drake Passage (Southern Ocean) with a description of eight new species and a review of the family Cladorhizidae in the Southern Ocean. Invertebrate Systematics, 31 (1), 37 - 64. https: // doi. org / 10.1071 / IS 16020"]}